Implant success and safety of left atrial appendage occlusion in end stage renal disease patients: Peri-procedural outcomes from an Italian dialysis population. (1st July 2018) - Genovesi, Simonetta; Slaviero, Giorgio; Porcu, Luca; Casu, Gavino; Bertoli, Silvio; Sagone, Antonio; Pieruzzi, Federico; Rovaris, Giovanni; Buskermolen, Monique; Danna, Paolo; Montoli, Alberto; Oreglia, Jacopo; et al.
Abstract: Aims: To estimate the safety and the efficacy of the off label left atrial appendage (LAA) occlusion in chronic dialysis patients with atrial fibrillation (AF). In this preliminary paper, we report the design of the study and the data on peri-procedural complications. Methods: This is a prospective cohort study. Primary endpoints are i) incidence of peri-procedural complications, ii) cumulative incidence of two-year thromboembolic events iii) cumulative incidence of two-year bleedings iiii) mortality at two years. Adverse events and death within 30 days of the procedure were recorded. Results: Fifty patients who underwent LAA occlusion between May 2014 and September 2017 were recruited. Both the mean age of the sample study and the dialysis duration were high [71.8 (9.6) years and 59.4 (78.2) months, respectively]. Most patients (84%) were hypertensive and 62% suffered a previous major bleeding. About half of them presented cardiovascular diseases. CHA2 DS2 VASCs and HASBLED scores were 4.0 (1.5) and 4.4 (0.9), respectively. Most patients (88%) showed atrial dilatation and 44% left ventricular hypertrophy; 32% had left ventricular ejection fraction <50%. Fifty five percent of patients had permanent AF and 32% paroxysmal AF. All devices were implanted successfully. No deaths or major adverse events were reported during a 30-day follow-up. Three episodes of peri-procedural access site bleeding were reported, requiring no transfusion. Conclusions: Our preliminary data suggest the feasibility and safety of LAA occlusion in patients undergoing dialysis. Only the follow-up of these patients over time can provide evidence that LAA occlusion is effective in preventing of thromboembolic events in this very high-risk population. Highlights: Oral anticoagulant therapy dramatically increases the risk of bleeding in patients with atrial fibrillation and end-stage renal disease. There is no evidence regarding the safety and efficacy of left atrial appendage occlusion in end stage renal disease population. Our data suggest that left atrial appendage occlusion is feasible with a good safety profile in end stage renal disease patients.